Case Report: Successful application of modified laparoscopic assisted percutaneous gastropexy in a dog using two 6-mm portal sites - Youn, Sohee; Kwak, Ho Hyun; Yoon, Seung Jun; Kim, Junhyung; Woo, Heung Myong (Frontiers in Veterinary Science, 2025)
Gastric dilatation and volvulus (GDV) is a life-threatening disease in dogs and has a high rate of recurrence without gastropexy. However, prophylactic gastropexy effectively reduces the incidence of GDV. In a 5-year-old female Russo-European Laika, who had a high risk of GDV due to being purebred and deep-chested, and a positive family history, prophylactic gastropexy—utilizing two 6-mm ports and barbed sutures—was performed using the modified laparoscopic-assisted percutaneous gastropexy (mLAPG) technique, without open celiotomy and intracorporeal suturing. The gastropexy suturing time was 29 min. Follow-up assessments using ultrasonography, laparoscopy, and endoscopy were conducted 1 month postoperatively and confirmed stable adhesion without gastric wall damage or complications at the gastropexy site. This is the first case report of the application of mLAPG in a dog. Based on the successful formation of adhesion and the absence of complications for 1 year in this case, the mLAPG technique can be recommended as an effective method for prophylactic gastropexy in dogs.